Effective and Engaging Active Learning in the Medical School Classroom: Lessons from Case-Based Collaborative Learning - Henrike C. Besche; Randall W. King; Keri M. Shafer; Sarah E. Fleet; Julia F. Charles; Tamara B. Kaplan; Katie A. Greenzang; Melanie P. Hoenig; Richard M. Schwartzstein; Barbara A. Cockrill; Krisztina Fischer (Journal of Medical Education and Curricular Development)
Large group collaborative teaching approaches are rapidly gaining popularity in undergraduate medical education. The case-based collaborative Learning (CBCL) pedagogy was instituted for pre-clerkship teaching at Harvard Medical School in 2015 with subsequent implementation at other medical schools. CBCL emphasizes inductive reasoning, integrates basic and clinical sciences, stimulates curiosity, and fosters teamwork. Given the ongoing educational evolution, guidance on designing and facilitating collaborative learning sessions, such as CBCL may benefit faculty in their instructional design efforts. This perspective article describes strategies to create effective collaborative sessions using CBCL as an example. We reviewed the literature and summarized ten years of experience in CBCL teaching through the lens of contemporary theories of teaching and learning. The recommendations are organized into three main domains: Instructional Design, Facilitation, and Professional Transformation, each aligned with the theoretical principles of CBCL. The recommendations provide a conceptual model to assist faculty in designing engaging and effective class materials and support students’ professional transformation during collaborative learning sessions.